A Survey Of Isozyme Polymorphism In Laboratory Population Of S.Dux (Diptera, Sarcophagidae) - KIRAN SINGH; SASYA THAKUR (International Journal of Pharma and Bio Sciences, 2012)
A survey of isozyme polymorphism among glucose and non-glucose metabolizing enzymes was carried out in the laboratory population of Sarcophaga dux. Polymorphic levels were found to be within the range recorded for other dipterans. Polymorphism among glucose-metabolizing enzymes were found to be on an average less variable (Ho=0.186; He=0.163) than the non-glucose metabolizing enzymes (Ho=0.275; He=0.485). Out of five loci, three loci (LDH-1, ACPH-1 and APH-1) were found to be polymorphic and these displayed significant deficiency of heterozygotes. These results supported the earlier findings that the substrate-specific enzymes with functional constraints have lower heterozygosity than the non-specific enzymes. They also added to the evidence obtained from other animals like Drosophila, echinoderms and some fish species.